360. A Case Control Study of COVID-19 in Patients with End Stage Renal Disease (ESRD). (31st December 2020) - Lim, Su Lin; Chan, Kok Hoe; Lagudu, Sudha; Szabela, Maria; Slim, Jihad
Abstract: Background: COVID-19 is a major global pandemic. Since the first case reported in Wuhan, China, COVID-19 has spread across the globe with more than 7.6 million individuals affected worldwide. Several studies have tried to investigate the risk factors for mortality but there has bot been a definitive study in patients with ESRD. Herein, we aimed to investigate whether ESRD is associated with mortality as compared to age, gender and comorbidities matched cohorts. Methods: A retrospective case control study was performed on patients 18-year-old with confirmed SARS-CoV-2 admitted to our hospital during the study period (03/15/2020 to 05/15/2020). Demographic, characteristics and clinical outcome were retrieved and reviewed. We found 39 ESRD patients, we matched them for 5 variables: Age, gender, diabetes mellitus (DM), hypertension (HTN), and body mass index (BMI). Age was stratified into 3 groups (< 30, 30 to 60, >60), history of DM and HTN were defined by reviewing the admission medications, and BMI was divided into 2 categories (< 30 and 30 kg/m2). The primary endpoint was percentage of inpatient mortality. Results: We had 39 ESRD patients with COVID-19 out of the 400 patients admitted during the study period with known clinical outcome. Nineteen patients (49%) were between 30 to 60 years old while the rest (51%) were older than 60 years old. As for gender, 25 (64%) were males and 14 (36%) females. Additional comorbidities were present in 38 patients with hypertension (92%) being the most common, followed by DM (64%) and BMI >30 kg/m2 (49%). With the 5 variables, we were able to match with 177 controls. Nineteen individuals expired out of the 39 ESRD patients (49%), as compared to 46 patients from the 177 matched cohort (26%) (z-score 2.80, p=0.0051; odds ratio [OR], 2.71; 95% confidence interval [CI], 1.28–5.41). Conclusion: Our results suggest that ESRD patients is an independent risk factor for increased mortality in patients with COVID 19 disease. Larger prospective studies will need to confirm this finding and try to find ways to mitigate this very high mortality in this vulnerable population. Disclosures: Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau)